2014
DOI: 10.3389/fped.2014.00011
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Kyphosis is Now Uncommon Amongst Children and Adolescents with Cystic Fibrosis

Abstract: Historically, thoracic kyphosis has been reported to be common amongst patients with cystic fibrosis (CF). The mechanisms leading to the development of this abnormality of the chest wall are not fully understood. In order to explore the prevalence of the condition amongst children with CF in the early twenty-first century and to explore factors that might be contributing to its development, a retrospective cross sectional study was undertaken in a regional CF unit. Data were obtained from 74 children with CF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
(13 reference statements)
1
6
0
1
Order By: Relevance
“…5 In rapidly growing teenagers, abnormal flexion of the spine impedes development of the viscera, and exaggerated thoracic kyphosis is associated with altered respiratory function. 6 In addition, hyperkyphosis can affect a teenager’s posture and appearance and may therefore impact their physical and psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…5 In rapidly growing teenagers, abnormal flexion of the spine impedes development of the viscera, and exaggerated thoracic kyphosis is associated with altered respiratory function. 6 In addition, hyperkyphosis can affect a teenager’s posture and appearance and may therefore impact their physical and psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the incidence of low back pain is high among Chinese adolescents and that spinal morphology (such as thoracic kyphosis) and spinal function (lumbar mobility) are correlated with nonspecific low back pain [9]. Furthermore, the sagittal morphology of the spine could negatively affect the pulmonary function among children and adolescents with certain specific diseases, such as cystic fibrosis and adolescent idiopathic scoliosis [10,11]. Although evidence is lacking, it could be inferred that this phenomenon may also affect healthy children and adolescents.…”
Section: Introductionmentioning
confidence: 88%
“…La plus grande fréquence de déformations rachidiennes, et notamment des cyphoses, a été décrite par le passé chez des patients dont l'état clinique était beaucoup moins bon [5]. Avec l'amélioration de l'état clinique des patients, ces complications sont devenues beaucoup plus rares [6,7]. À l'âge adulte, ces complications ostéo-articulaires augmentent la morbidité liée à la MV : pneumothorax en cas de fracture costale, douleurs, limitation de l'activité physique, diminution de l'ampliation thoracique et altération de la fonction respiratoire, limitation des manoeuvres de kinésithérapie respiratoire.…”
Section: Définitionunclassified